IFT and Chebyshev-based planar array thinning for adaptive interference suppression - Agha, Maryam H.; AL-Adwany, Maan A. S.; Bayat, Oguz; Hamdoon, Hind Th (Journal of computational electronics, 2023)
Smart antenna arrays with adaptive nulling capability are emerging as a promising solution to suppress the interference in radar applications and wireless communications in real time. Many adaptive nulling methods have been commonly used, such as controlling amplitude or/and phase excitations of the antenna elements and controlling the position of the elements. Generally, most adaptive nulling methods demand digital beamforming to create the correlation matrix from signals that arrived to array antennas. The digital beamforming is costly and needs frequent calibration; therefore, it does not appropriate for large antenna arrays. Among adaptive nulling methods, an array thinning does not require digital beamforming. It takes advantage of the adaptive algorithm to make the element active or inactive. In this paper, an IFT and Chebyshev techniques-based random thinning is presented to suppress the interference adaptively by lowering the SLL or place nulls toward the interference direction. The proposed method works with the antenna arrays that have transmit/receive modules (TRM) with RF switches. The results show the ability of both IFT and Chebyshev techniques to suppress the interference for the small array. In addition, the results indicate the superiority of IFT technique over Chebyshev in the large arrays; it is considerably faster and more efficient (in terms of lowering the sidelobe levels and nulls formation) than the Chebyshev technique. The advantage of the proposed method is no digital beamforming is needed. Consequently, a considerable reduction in complexity, power consumption, and cost can be attained.